Arbuscular Mycorrhizal Fungi Promote the Degradation of the Fore-Rotating Crop (Brassica napus L.) Straw, Improve the Growth of and Reduce the Cadmium and Lead Content in the Subsequent Maize - Guo, Jianfang; Chen, Jiaxin; Li, Chengxue; Wang, Lei; Liang, Xinran; Shi, Junjie; Zhan, Fangdong (Agronomy (Basel), 2023)
Arbuscular mycorrhizal fungi (AMF) are widely present in heavy metal-polluted soils, but their effects on straw degradation and plant growth of rotated crops are poorly understood. In this study, a pot experiment was used to simulate the return of fore-rotating crop (Brassica napus L.) straw to farmland with a subsequent planting of maize in a lead–zinc mining area on the Yunnan Plateau, Southwest China, which included four treatments: control (CK), addition of rape straw (SR), inoculation of AMF (AMF), and both AMF inoculation and straw addition (AMF + SR). The effects of AMF on the degradation and nutrient release of the fore-rotating rape straw and the growth, mineral nutrition and the cadmium (Cd) and lead (Pb) contents of the subsequent maize were investigated. Compared with the CK treatment, AMF significantly promoted the degradation of rape straw and the release of mineral nutrients (nitrogen, phosphorus and potassium) as well as the Cd and Pb, increased the content of available nutrients in soil, and improved the mineral nutrient contents in the maize. AMF + SR significantly increased the maize height and biomass by 32–35% and decreased the available Cd and Pb contents in soil and the Cd and Pb contents in the maize by 20–30% and 18–25%, respectively. Moreover, the available Cd and Pb contents in the soil presented significant positive correlations with their contents in the maize but negative correlations with the height and biomass of the maize. Thus, AMF played an important regulatory role in the nutrient cycling and heavy metal accumulation of the crop rotation.